(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The media, in particular, is becoming increasingly prevalent in political discourse. Recentstudies have shown that micro blogging websites such as twitter may increase political engagement, whilesocial networking sites such as facebook can do the same. In addition to Twitter, political organizationshave started using Facebook pages or groups to engage directly with individuals and encourage greaterpolitical conversation. In today’s digital era, social media is a powerful tool for sharing information. In thisstudy, researchers will examine the use of social media in political campaign management. During the2014 midterm elections, social media had a significant impact on voting behavior. In 2014 and beyond,there were several start-ups connected to social media. It was inevitable that their tenure would finish onMay 31, 2014, as the 15th Lok Sabha elections were held in April and May of 2009, respectively. TheElection Commission of India (ECI) split up India’s election process into many parts for security andlogistical considerations. Voting behavior and enhancement of political party spending on social mediafor campaign management will be evaluated as part of the study